2019
DOI: 10.1126/sciadv.aav0693
|View full text |Cite
|
Sign up to set email alerts
|

New tolerance factor to predict the stability of perovskite oxides and halides

Abstract: Simple and interpretable data-driven descriptor accurately predicts the synthesizability of single and double perovskites.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
786
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,004 publications
(799 citation statements)
references
References 45 publications
(108 reference statements)
9
786
1
3
Order By: Relevance
“…For example, Sun and Yin have shown that (μ + t ) η , where η is the atomic packing fraction, showed a better linear relationship with the thermodynamic stability of 138 perovskites. More recently, Bartel et al have proposed a new tolerance factor τ encompassing both halide and oxide perovskites after SISSO feature selection as the following τ=rXrBnAnArA/rBlogrA/rB where n A is the oxidation state of A. Using the criteria of τ < 4.18 for stable perovskites, this new tolerance factor can separate perovskites versus nonperovskite in an experimental data set of 576 ABX 3 with an accuracy of 92%.…”
Section: Applicationmentioning
confidence: 99%
“…For example, Sun and Yin have shown that (μ + t ) η , where η is the atomic packing fraction, showed a better linear relationship with the thermodynamic stability of 138 perovskites. More recently, Bartel et al have proposed a new tolerance factor τ encompassing both halide and oxide perovskites after SISSO feature selection as the following τ=rXrBnAnArA/rBlogrA/rB where n A is the oxidation state of A. Using the criteria of τ < 4.18 for stable perovskites, this new tolerance factor can separate perovskites versus nonperovskite in an experimental data set of 576 ABX 3 with an accuracy of 92%.…”
Section: Applicationmentioning
confidence: 99%
“…introduced the factor called atomic packing fraction ( η ) that is comparatively correlated with decomposition energy (Δ H D ) use to predict the thermodynamic stability of double perovskites with an accuracy of 86 %. Bartel et al . recently introduced a new tolerance factor (τ )> trueτ=normalrnormalXnormalrnormalB-nA()normalnnormalA-normalrnormalA/normalrnormalBlnrA/rB, …”
Section: Crystal Structure and Band Diagram Of Lead‐free Double Perovmentioning
confidence: 99%
“…Among them, the perovskite‐type hydrides have been promising candidate for solid‐state type of future hydrogen storage materials . There are numerous number of perovskite compounds that can be obtained as carbides, nitrides, fluorides, chlorides, bromides, oxides, hydrides, and iodides . On the other hand, oxides and hydrides are the most prominent structures which may be applicable in the use of hydrogen storage …”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23][24][25][26][27][28] There are numerous number of perovskite compounds that can be obtained as carbides, nitrides, fluorides, chlorides, bromides, oxides, hydrides, and iodides. 29,30 On the other hand, oxides and hydrides are the most prominent structures which may be applicable in the use of hydrogen storage. 24 ABH 3 compounds may be separated into two groups: In the first group, A and B elements can be chosen from group I and II elements of periodic table, respectively.…”
Section: Introductionmentioning
confidence: 99%